Integrative description of a new species of Lauratonemella Tchesunov, 1984, and phylogenetic insights - Suman Patra; Daniel Leduc; Shesdev Patro (Marine Biodiversity, 2026)

Description of a New Species of the Genus Ceramonema Cobb, 1920 (Plectida: Ceramonematidae) from India - Suman Patra; Shesdev Patro (Thalassas: An International Journal of Marine Sciences, 2026)

Meiofauna and nematode communities in a sandy beach and in the sandbars of an adjacent creek on the Odisha coast, India - Panda Narayan; K.U. Abdul Jaleel; Shesdev Patro; R. Jyothibabu; Sweta Beura; N. Srustishree (Regional Studies in Marine Science, 2026)

Description of a new species of the genus Elasmopus A. Costa, 1853 (Amphipoda: Maeridae) by morphological and molecular analysis - Shreeraj Nahak; Suman Patra; Shesdev Patro (Marine Biodiversity, 2026)

Spatio‐Temporal Dynamics of Benthic Amphipods in a Tropical Coastal Lagoon: Population Patterns and Environmental Correlations - Gitanjali Bhoi; Farzaneh Momtazi; Shesdev Patro (Marine Ecology, 2026)
This study provides the first detailed assessment of the spatio‐temporal distribution of benthic amphipods in Chilika Lagoon. Seasonal changes in species composition, diversity, and distribution were analyzed across four lagoon sectors, along with environmental factors influencing these patterns. Thirteen species belonging to seven genera and families were recorded, with Aoridae, Eriopisidae, and Maeridae being dominant. Permutational Multivariate Analysis of Variance (PERMANOVA) and Canonical Analysis of Principal Coordinates (CAP) analyses revealed clear separation between post‐monsoon/winter assemblages and those from pre‐monsoon/monsoon seasons. Amphipod communities differed markedly from earlier records, likely due to long‐term ecological changes in the lagoon, though Quadrivisio bengalensis and Victoriopisa chilkensis persisted, indicating their resilience. Principal Component Analysis (PCA) and Distance‐based Linear Models (DistLM) showed amphipod diversity significantly correlated positively with dissolved oxygen and pH, and negatively with depth and temperature. General Linear Model (GLM) identified dissolved oxygen as the primary driver that can model the amphipod distribution in the studied area. The results of Canonical Correspondence Analysis (CCA) demonstrated that amphipod species show varying degrees of specialization, with F. odishi exhibiting a strong environmental affinity, while most taxa display broader ecological tolerance. In contrast, Quadrivisio bengalensis , Quadrivisio chilikensis , and Ampelisca sp. were associated with higher temperature and higher total organic carbon (TOC). Overall, this study establishes a much‐needed ecological baseline for benthic amphipods in Chilika Lagoon, demonstrating the species‐specific responses to environmental conditions and offering a framework for detecting future ecological change.

Range Extension of Checkered Goby Gobiopsis canalis Lachner & McKinney, 1978 (Gobiiformes: Gobiidae) to Northeastern Indian Ocean - Suman Patra; Dipanjan Ray; Shesdev Patro; Anil Mohapatra (Thalassas: An International Journal of Marine Sciences, 2023)

Preliminary assessment of the water quality of Rushikulya estuary based on the abundance of pathogenic bacteria - Bhubaneswari Panda; Lokeshwara Sundaray; Ankita Mishra; Subhadarshani Palai; Sanjukta Rani Padhi; Shesdev Patro; Pratap Kumar Mohanty (Environmental Monitoring and Assessment, 2023)

Morphological and molecular clue resolves confusion in Pisodonophis boro complex with re-description of Pisodonophis boro (Hamilton 1822) from type locality and description of a new species from India - Swarup Ranjan Mohanty; Rajesh Kumar Behera; Smrutirekha Acharya; Lipika Patnaik; Dipanjan Ray; Jaya Kishor Seth; Shesdev Patro; Subhrendu S. Mishra; Anil Mohapatra (Marine Biodiversity, 2023)

First Record of Stolephorus mercurius Hata et al. 2021 (Cluepeiformes: Engraulidae) from Indian Ocean with a Note and Key to Identification of Indian Ocean Species of the Genus Stolephorus Lacepède 1803 - Rajeswari Gouda; Suman Patra; Shesdev Patro; Subhrendu Sekhar Mishra; Anil Mohapatra (Thalassas: An International Journal of Marine Sciences, 2023)

Marine Benthic Amphipods (Amphipoda) of India: An Assessment on their Biodiversity, Distribution and Significance - Gitanjali Bhoi; Sourabh Kumar Dubey; Shesdev Patro (Thalassas: An International Journal of Marine Sciences, 2023)

Research Communication - Shesdev Patro; Sunil Kumar Padhi; Gitanjali Bhoi; Siba Prasad Parida; Anil Mohapatra; P. Krishnan (Thalassas: An International Journal of Marine Sciences, 2022)

New Distributional Record of Moringua raitaborua (Hamilton, 1822) - First Record of the Genus in the Chilika Lagoon, India - Rajesh Kumar Behera; Swarup Ranjan Mohanty; Shesdev Patro; Anil Mohapatra (Thalassas: An International Journal of Marine Sciences, 2021)

Diversity of gastropods and bivalves in the mangrove ecosystem of Paradeep, east coast of India: a comparative study with other Indian mangrove ecosystems - Ranjana Yadav; Pratyush Kumar Malla; Damini Dash; Gitanjali Bhoi; Shesdev Patro; Arunendra Mohapatra (Molluscan Research, 2019)